Forming a System of Indicators Showing the State and Development of «Smart» Cities in Ukraine - Korepanov Oleksiy S.; Chala Tеtyana G.; Korepanov Georgii S.; Chernenko Daryna I.; Maslov Mykola U. (Problemi Ekonomiki, 2021)
The article is aimed at studying international experience and on this basis substantiating the feasibility of calculating and using an index of living conditions and urban development in Ukraine. It is determined that a number of indices are calculated at the international level, making it possible to obtain an integrated assessment of the cities in the world, namely: The Global Cities Index, developed by Kearney; Cities in Motion Index, developed by IECE; Global Financial Centers Index, developed by Z / Yen; Global Power City Index, developed by the IMF; Global Liveability Ranking, proposed by The Economist. The positions of the 10 best cities-2019 in the world are compared according to the five described indices. It has been determined that such cities as London, New York, Paris, Tokyo, and Hong Kong are often ranked among the top 10 most prosperous cities or cities with the highest living standards in the world. It is determined that to precisely elaborate and use the technique for calculating the relevant indices for Ukrainian cities it is advisable to choose the Cities in Motion Index, because, unlike other indices, it has a wide geographical coverage, analyzes the largest number of cities, including Kyiv, and takes into account the maximum number of indicators. It assesses such socio-economic aspects of urban development, as human capital, economy, ecology, social cohesion, governance, mobility and transport, urban planning, international reach and technology. A corresponding sub-index is calculated for each aspect. Using the methodological provisions of the CIMI calculation, the values of sub-indices for the city of Kharkiv have been calculated, and the integral value of the index has been obtained, thus determining Kharkiv’s position in the world ranking